Review Article : Potensi Aktivitas Antioksidan Dari Berbagai Tanaman Untuk Tabir Surya - Himyatul Hidayah; Mentari Mentari; Ainun Mar’atus Putri Warsito; Dinda Dinanti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Sunscreen is a cosmetic preparation which is usually used as a treatment for the skin to prevent free radicals and protect the skin from the dangerous sunglight.. Many Activite compund in plants that have antioxidant activity are believed to be able to ward off both free radicals and exposure to sunlight. From the research of literature review, it aims to determine the relationship between potential antioxidant activity in plants for sunscreen cosmetic preparations. The method of research is searching the databases from various articles like Google Scholar, ResearchGate, PubMed. The results showed that the active substances from various plants have the potential as antioxidants that can be used as sunscreens to protect the skin from radicals and sunlight